1999
DOI: 10.1083/jcb.144.2.225
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Differences in the Appearance of NEP-B78 and an LBR-like Protein during Xenopus Nuclear Envelope Reassembly Reflect the Ordered Recruitment of Functionally Discrete Vesicle Types

Abstract: In this work, we have used novel mAbs against two proteins of the endoplasmic reticulum and outer nuclear membrane, termed NEP-B78 and p65, in addition to a polyclonal antibody against the inner nuclear membrane protein LBR (lamin B receptor), to study the order and dynamics of NE reassembly in the Xenopus cell-free system. Using these reagents, we demonstrate differences in the timing of recruitment of their cognate membrane proteins to the surface of decondensing chromatin in both the cell-free system and XL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 42 publications
4
61
0
Order By: Relevance
“…Whether this is due to lateral diffusion within the membrane or to vesicle formation and fusion is an open question. In certain cases, extensively exemplified by Xenopus eggs, integral membrane proteins of the nuclear membrane are found in distinct vesicles (Vigers and Lohka, 1991;Buendia and Courvalin, 1997;Drummond et al, 1999). Indeed, recent reports suggest that there are multiple populations of specialized vesicles (Antonin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Whether this is due to lateral diffusion within the membrane or to vesicle formation and fusion is an open question. In certain cases, extensively exemplified by Xenopus eggs, integral membrane proteins of the nuclear membrane are found in distinct vesicles (Vigers and Lohka, 1991;Buendia and Courvalin, 1997;Drummond et al, 1999). Indeed, recent reports suggest that there are multiple populations of specialized vesicles (Antonin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…By biochemical methods, it was also shown that nuclear vesicles in mitosis were heterogeneous (Vigers and Lohka, 1992;Chaudhary and Courvalin, 1993;Lourim and Krohne, 1993;Buendia and Courvalin, 1997;Drummond et al, 1999). In the present paper, we prepared antibody against p60, a protein in LVs, to confirm the biochemical differences between LVs and HVs.…”
Section: Discussionmentioning
confidence: 67%
“…3B, lower). However, LBR-containing vesicles were incorporated into the nuclear envelope (Drummond et al, 1999). Thus, LBRcontaining HVs must bind to sperm-binding LVs to incorporate into the nuclear envelope before fusion events occur.…”
Section: Salt-treated Hvs Bind To Lvsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that in vitro nuclear assembly spontaneously in Xenopus egg interphase extracts a double nuclear membrane with nuclear pore forms around added chromatin, whether natural animal or plant sperm chromatin or exogenously added procaryotic DNA is used [3][4][5]. Some information concerning reassembly of nuclear membranes, organelles, and individual nucleosomes has arisen from the use of cell-free extracts derived from eggs of Xenopus or sea urchin, and somatic cells and embryos of Drosophila or Nicotiana [2,[6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%